Earthworm Infusion as an Antimicrobial Against Bacteria Causing Diarrhea - Masyhuda, Irmawati; Nikmatullah, Nurul Azmah (Fakultas Kedokteran UPN Veteran Jakarta Kerja Sama KNPT, 2024)
Diarrhea is the second most common disease worldwide after Acute Respiratory Infection (ARI). One of the causes of diarrhea is the gastrointestinal infection caused by disease bacteria (microbe) such as Salmonella sp., Escherichia coli, Shigella sp., and Vibrio cholerae. The earthworm species Lubricus sp can be used as an alternative medication believed to be able to cure digestive diseases such as typhus, dysentery, and other indigestion like gastritis. This research is laboratory experimental research. The antibacterial activity is measured by determining the Minimum Inhibitory Concentration (MIC) and Minimum Bactericidal Concentration (MBC) values of earthworm infusion (Lumbricus rubellus) using the tube dilution test. The bacteria used in this research are Escherichia coli, Shigella dysentriae, and Vibrio cholerae, isolated from the feces of diarrhea patients. This research aims to examine the earthworm infusion antibacterial (Lumbricus rubellus) activity to several bacteria that commonly cause diarrhea. The research results show that the average MIC value of earthworm infusion (Lumbricus rubellus) against Escherichia coli is >50%, Shigella dysentriae 0,098%, and Vibrio cholerae >50%. The average MBC value of earthworm infusion against Shigella dysentriae is 50%. .